Penggunaan Metode Pembelajaran Turjuman Al-Quran dalam Pendidikan Karakter Siswa Sebagai Respons Terhadap Modernisasi dan Globalisasi - Syaibani, Izatul A’yun; Rohman, Moh. Fatkur (Medan Resource Center, 2025)
The Modernization and globalization are proof of the development and progress of human civilization that occurred in the 20th century. Advances in information technology, the occurrence of global development and progress, to paradigm shifts that occur in all sectors of life, are of particular concern to Indonesia, especially for Islamic education. Islamic education faces great challenges with the entry of foreign cultures through easy access to information technology and social media, which then has a negative impact on students in schools. In the end, the level of juvenile delinquency is increasing. In this study, researchers attempted to formulate a concept of Islamic education learning by using the Turjuman al Quran method as a method of understanding character education to students. Turjuman has several steps as a way to understand the Quran. The result is that the teacher has the task of determining the character education materials contained in the Quran, then using the Turjuman method in providing understanding to students at school.